Theoretical deliberations on frontier location of cities. - Brzosko-Sermak, Agnieszka (Bulletin of Geography. Socio-economic Series, 2007)
Nowadays political and socio-economic reorganization of the European space, where cities play a very important role, has a strong impact on peripheral areas, referred to as border regions. One can observe a changing role of these regions due to various functions and effects of internal or external borders in the integrated Europe. Internal border cities have gained new functions and a chance for the development. However, cities in the external European border regions may face serious development barriers which can result in the economic recession unless they can develop transportation or trade functions and thus become gateway cities.